HUBUNGAN TRUST IN BRAND TERHADAP LOYALITAS PELANGGAN TELKOMSEL - Siregar, Indah Permatasari (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
Telkomsel is a company operating in the cellular telecommunications sector in Indonesia which strives to be a trusted provider of services and lifestyle solutions. Telkomsel is not the only company that offers cellular card products, there are many other products that have lower quality and prices. However, Telkomsel always dominates the market and has the highest number of customers. The formulation of the problem in the research is whether there is an influence of trust in the product brand on Telkomsel customer loyalty among students at the Faculty of Islamic Economics and Business, Syekh Ali Hasan Ahmad Addary University, Padangsidimpuan. The aim of the research is to find out how much influence Trust in Product Brand has on Telkomsel Customer Loyalty. This research is quantitative research consisting of the dependent variable, namely Trust In Brand. The sample used in this research was 100 respondents. The data collection technique uses the Questionnaire method. Data analysis was done using linear regression analysis and supported by validity tests, reliability tests, normality tests, linearity tests, classical assumption tests and t tests, while data management was assisted by the SPSS Version 26.0 program. The research results show that Trust in brand has a partial effect on customer loyalty.